Ethical problems and their resolution amongst UK community pharmacists: a qualitative study - Cooper, Richard (2007)
This thesis explores what UK community pharmacists experience as ethical problems in their work, how they try to resolve such problems and how the community pharmacy setting may be of influence. Utilising existing normative ethical theories, but acknowledging the status of empirical ethics research and also the social context of ethical problems, semi-structured interviews were conducted with a purposive sample of twenty three community pharmacists from the north of England, UK. It was found that pharmacists encountered ethical problems in the routine minutiae of dispensing prescriptions and medicines sales. Ethical problems often involved legal and procedural concerns and could be distinguished from philosophical dilemmas and many pharmacists understood law and ethics synonymously. Ethical passivity emerged as a description of pharmacists who were ethically inattentive, displayed legalistic self-interest and failed to act ethically. Ethical reasoning was often incomplete and involved appeals to consequences, the golden rule, common sense and religious faith. Some pharmacists were ethically active and sensitive to ethical issues and experienced ethical doubt and uncertainty. The code of ethics and the advice of professional bodies were not considered helpful. The community pharmacy setting precipitated ethical problems and was inimical to ethical practice since pharmacists' relative isolation from others precluded ethical discussion and relationships; pharmacists' subordination to doctors precipitated problems and vitiated ethical responsibility; routinization of pharmacists' work meant difficult ethical situations could be avoided. The findings of this thesis raise questions as to how pharmacists can be effectively educated in ethical issues at an under- and post-graduate level; how values can be adequately transmitted within the profession given the ineffectiveness of the code of ethics; whether pharmacists are ethically prepared for new primary care roles; and whether isolation and subordination may be ethically problematic in healthcare more generally.